2013
DOI: 10.3892/ijo.2013.2137
|View full text |Cite
|
Sign up to set email alerts
|

Parthenolide induces superoxide anion production by stimulating EGF receptor in MDA-MB-231 breast cancer cells

Abstract: Abstract. The sesquiterpene lactone parthenolide (PN) has recently attracted considerable attention because of its antimicrobial, anti-inflammatory and anticancer effects. However, the mechanism of its cytotoxic action on tumor cells remains scarcely defined. We recently provided evidence that the effect exerted by PN in MDA-MB-231 breast cancer cells was mediated by the production of reactive oxygen species (ROS). The present study shows that PN promoted the phosphorylation of EGF receptor (phospho-EGFR) at T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…It was observed that most of the cells were positive to DCF signal already at 1-3 h of treatment. Since this effect was suppressed by the addition of either apocynin or DPI, two effective inhibitors of NOX activity, we suggest that parthenolide, in line with previous findings (13,15), stimulated NOX activity, inducing production of O 2…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…It was observed that most of the cells were positive to DCF signal already at 1-3 h of treatment. Since this effect was suppressed by the addition of either apocynin or DPI, two effective inhibitors of NOX activity, we suggest that parthenolide, in line with previous findings (13,15), stimulated NOX activity, inducing production of O 2…”
Section: Discussionsupporting
confidence: 69%
“…In previous studies (13,15), we showed that parthenolide induces generation of ROS in MDA-MB-231 cells. The aim of the present study was to individuate the ROS produced under parthenolide treatment to specify the modalities of their production and the role exerted in the induction of cell death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AG1478 is an EGFR selective inhibitor that principally blocks EGFR activation at Tyr1173 (28,29). In the present study, AG1478 increased AGS cell apoptosis, thus we speculate that the expression levels of EGFR may be associated with its activity.…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of estrogen, progesterone, and epidermal growth factor type 2 receptors (ER, PgR, and HER2, respectively) is widely used in clinical practice in order to obtain prognostic and predictive information [24]. Also, several other markers, such as B-cell lymphoma 2, androgen receptor, EGF, phosphatase and tensin homolog (PTEN), and phosphatidylinositol 3-kinase (PI3K), may have prognostic value in breast cancer.…”
Section: An Overview On Main Signaling Pathways Involved In Breast Camentioning
confidence: 99%